Agricultural land use and food safety - Nagy, János (Acta Agraria Debreceniensis, 2014)
The world’s food production needs to be doubled in order to cover the need of the population by 2050 even if it exceeds 9 billion. The output of agriculture is expected to increase by 1.7% every year until 2020 (OECD, FAO 2011) which is a major decrease in comparison with the average 2.6% increase of the previous decade. At the same time, the meat, dairy, sugar and vegetable oil consumption is likely to increase by 2020 to a higher extent than so far. Due to the increasing food prices, the amount of starving people will increase and food consumption will decrease – especially in developing countries – as people will be able to buy less and only cheaper food products. Also, obesity may become a more severe problem and the inequality of the population’s health status could increase.One of the most important elements of adapting to global climate change is food safety; therefore, it is especially important to breed new biological bases and to introduce production systems which contribute to adapting to changed circumstances.